Emission properties of textured gallium nitride with high density of stacking faults. (December 2020) - Mynbaeva, M G; Ivanova, E V; Kirilenko, D A; Smirnov, A N; Mynbaev, K D
Abstract: In this study we related structural properties of GaN grown on ceramic substrate and studied with transmission electron microscopy with the results of photo-and cathodoluminescence investigations. We found that stacking faults in the basal plane were responsible for both strong room temperature visible emission and exciton-related ultraviolet luminescence at cryogenic temperature.